An evaluation of the various conservation techniques employed by selected academic institutions in Metro Manila for archival print materials - Realeza, Aileen S. (Institute of Library Science, University of the Philippines Diliman, 2001)
The study was an evaluation of the various conservation techniques employed by selected academic institutions in Metro Manila for their archival materials in paper. The institutions involved were the Ateneo de Manila University Library Archives (ADMULA), the Archives of the University of Santo Tomas (AUST), the De La Salle University Archives (DLSUA), and the University of the Philippines Archives and Records Depository (UARD).